2009
DOI: 10.1063/1.3183777
|View full text |Cite
|
Sign up to set email alerts
|

Liquid plug propagation in flexible microchannels: A small airway model

Abstract: In the present study, we investigate the effect of wall flexibility on the plug propagation and the resulting wall stresses in small airway models with experimental measurements and numerical simulations. Experimentally, a flexible microchannel was fabricated to mimic the flexible small airways using soft lithography. Liquid plugs were generated and propagated through the microchannels. The local wall deformation is observed instantaneously during plug propagation with the maximum increasing with plug speed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…Also, plug rupture and reformation at airway bifurcations could be different from those in the tubular sections of the airway (21). Interaction between plugs and the airway walls during air ventilation would also need to be carefully studied to enable more accurate liquid delivery in actual lungs (21,42). Although it would be technically challenging, the contact angles of liquid plugs and collars would need to be more precisely determined in the airways, especially within distal airways and alveoli.…”
Section: Discussionmentioning
confidence: 99%
“…Also, plug rupture and reformation at airway bifurcations could be different from those in the tubular sections of the airway (21). Interaction between plugs and the airway walls during air ventilation would also need to be carefully studied to enable more accurate liquid delivery in actual lungs (21,42). Although it would be technically challenging, the contact angles of liquid plugs and collars would need to be more precisely determined in the airways, especially within distal airways and alveoli.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical simulations of liquid plug propagation in a rigid channel (Fujioka & Grotberg 2004Fujioka, Takayama & Grotberg 2008) confirmed that sharp peaks in wall stresses and stress gradients were present in the transition region of the plug during plug propagation. In addition, experimental and numerical studies of plug propagation in flexible microchannels (Zheng et al 2009) predicted a higher level of wall stresses and stress gradients along a highly deformable wall as compared to a rigid channel wall.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, plug rupture imposed a higher risk of cellular injury than plug propagation alone. Additional experimental and theoretical studies on plug propagation in flexible microchannels by Zheng et al [26] indicate higher risk of injury for greater flexibility, which is a feature of airways in emphysema, for example.…”
Section: Introductionmentioning
confidence: 97%